The psychological mechanism of basic psychological need frustration affecting job burnout: a qualitative study from China - Shi, Hairong (Frontiers in Psychology, 2024)
Introduction Job burnout is a common issue in most professions, and it can have adverse effects on employees, their families, clients, and organizations. It is essential to address and resolve job burnout syndrome. More research is needed to understand the underlying psychological mechanisms involved in job burnout. This study introduces the concept of primary psychological need frustration to explore its impact on the psychological processes involved in job burnout. Methods This study adopted a qualitative research methodology based on purposive sampling and convenience sampling principles. Eight grassroots senior counselors with over 13 years of teaching experience at a Chinese university were selected as the study cases. The data were gathered through semi-structured interviews and analyzed thoroughly via cluster analysis, which involved examining the text data word by word, sentence by sentence, line by line, and fragment by fragment. NVivo 11 software was used to register and code the text data. Results The study revealed that the subjects experienced high levels of frustration with their basic psychological needs. This frustration was evident in the coexistence of negative job characteristics and a lack of autonomy, a hostile professional environment and a lack of competence, and the negative behavior of others and relationship frustration. The study also revealed that the four types of primary psychological need frustration were strongly linked to job burnout: A lack of control motivation or motivation, the pursuit of external goals, negative behavior patterns, and the causal orientation of a controlled style. These factors positively predicted various dimensions of job burnout and positively affected the frustration of basic psychological needs. Conclusion This study effectively explains the psychological process behind why individuals experience severe job burnout in a controlled organizational environment due to frustration with basic psychological needs. This study also highlights the internal causal relationship between primary psychological needs, frustration, and job burnout. This insight can help employees and organizations prevent and detect early job burnout syndrome and enhance employees’ occupational well-being and organizational vitality.